Revisiting the Conceptual Framework of Transitional Justice: Some Critical Notes - Al-Makassary, Ridwan (Kathmandu School of Law Review, 2013)
Scholars generally agree that transitional justice represents a framework of mechanisms that works to restore the rule of law and justice through both judicial and non-judicial responses. From the outset, transitional justice comprises a broad, complex and elusive conceptual framework. This is necessarily so because the measures to be employed vary from case to case and country to country. Likewise, adopting a mechanism that has been successful in one country will not necessarily achieve the same results in another country, or at another time once and for all. In this perspective, the article attempts to review the conceptual framework of transitional justice. It presents analytical description on transitional justice concerning definition, goals, development and comprehensive mechanisms.